Prevalence and Related Factors of Rupture among Cases with Ectopic Pregnancy; a Systematic Review and Meta‐Analysis - Xu , Chenchen; Mao , Zhilei; Tan , Mi; Mazhari , Seyed Amirhossein; Ghorbani Vajargah , Pooyan; Karkhah, Samad; Izadi , Fatemeh; Rouhi , Parisa (Archives of Academic Emergency Medicine, 2023)
Introduction: In the absence of timely treatment, the risk of rupture in patients with ectopic pregnancy (EP) increases, which is associated with extensive bleeding, complicated surgery, and maternal death. This study aimed to investigate the prevalence of rupture and its related factors among EP cases. Methods: A comprehensive, systematic search was conducted in electronic databases, such as Scopus, PubMed, Web of Science, and Persian electronic databases such as Iranmedex, and Scientific Information Database using keywords extracted from Medical Subject Headings such as "Ectopic pregnancies", "Extrauterine pregnancies", and "Ruptured ectopic pregnancy" from the earliest to the 13th of December 2022. The CMA program, version 3, was utilized for analysis. The overall effect size was calculated using the sample size and the frequency of rupture in each of the studies. Heterogeneity was measured using the I2 statistics. Results: A total of 5,269 women with EP participated in 17 studies. The pooled prevalence of rupture was 56.4% (95%CI: 44.9% to 67.2%; I2=98.09%; P<0.001). Factors such as number of parties, amount of β-hCG, age, history of ectopic pregnancy, cornual and isthmic pregnancies, gestational age, number of gravidities, history of tubal ligation, tubal diameters, periods of infertility, history of infertility, pregnancy by ovulation induction, extensive hemoperitoneum, ampullar and isthmic pregnancies, ampullar pregnancies, preoperative heart rate (HR), triage, triage shock index (SI), abdominal pain, single marital status, preoperative hemoglobin levels, preoperative hematocrit levels, history of pelvic inflammatory disease (PID), and use of contraceptives were associated with the prevalence of rupture in EP cases. Conclusion: Based on the findings, 56.4% of EP cases experienced rupture and various factors influence its prevalence. As a result, health managers and policymakers can address and mitigate modifiable factors contributing to rupture in EP cases by implementing regular consultations and screenings.